Fluorescent Zn(II)-Based Metal-Organic Framework: Interaction with Organic Solvents and CO2 and Methane Capture - Sifani Zavahir (1657531) (2022)
Adsorption of carbon dioxide (CO2), as well as many other kinds of small molecules, is of importance for industrial and sensing applications. Metal-organic framework (MOF)-based adsorbents are spotlighted for such applications. An essential for MOF adsorbent application is a simple and easy fabrication process, preferably from a cheap, sustainable, and environmentally friendly ligand. Herein, we fabricated a novel structural, thermally stable MOF with fluorescence properties, namely Zn [5-oxo-2,3-dihydro-5H-[1,3]-thiazolo [3,2-a]pyridine-3,7-dicarboxylic acid (TPDCA)] • dimethylformamide (DMF) •0.25 H2O (coded as QUF-001 MOF), in solvothermal conditions by using zinc nitrate as a source of metal ion and TPDCA as a ligand easy accessible from citric acid and cysteine. Single crystal X-ray diffraction analysis and microscopic examination revealed the two-dimensional character of the formed MOF. Upon treatment of QUF-001 with organic solvents (such as methanol, isopropanol, chloroform, dimethylformamide, tetrahydrofuran, hexane), interactions were observed and changes in fluorescence maxima as well as in the powder diffraction patterns were noticed, indicating the inclusion and intercalation of the solvents into the interlamellar space of the crystal structure of QUF-001. Furthermore, CO2 and CH4 molecule sorption properties for QUF-001 reached up to 1.6 mmol/g and 8.1 mmol/g, respectively, at 298 K and a pressure of 50 bars. Other Information Published in: Molecules License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/molecules27123845